PENGARUH EARNINGS PERSISTANCE, DIVIDEND POLICY DAN INVESTMENT POLICY TERHADAP FIRM VALUE - Wendy Salim Saputra; Lidya (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2024)
ABSTRACT The aim of this study is to test the influence of earnings persistence, dividend policy and investment policy on firm value. The analytical method used is a statistical method with a quantitative research type. In this research, to obtain a sample with a non-probability sampling method using a purposive sampling technique based on the LQ45 company annual report data accessed from the Indonesia Stock Exchange website with the observation year in the 2020-2022 period. In this study, there were 12 companies that met the sampling criteria and were used as samples. Data testing was carried out using SPSS 25 software with a multiple regression analysis model. The research results reveal that earnings persistence and investment policy have no effect on firm value, while dividend policy has an effect on firm value. Keyword: earnings persistance; dividend policy; investment policy; firm value